Improving Tourism in Lapland in the Low Season - Benjamin, Tom (Laurea-ammattikorkeakoulu, 2015)
The aim of this thesis is to develop ways that could improve tourism in Lapland in the low season. The author worked in co-operation with the safari company Safartica in Ylläs in Lapland. The company was used as a model for the analysis and development of ideas as a basis for this thesis. The theoretical framework consists of introductions into tourism in Finland and especially Lapland. The study analyses the current trends of the region and how it is marketed to both domestic and foreign markets. Working with Safartica the author will explore the development of the business and the tourism segment the company operates in while suggesting new avenues for possible development that could be implemented in the low season. The quantitative research method was used in the empirical part of the thesis and a questionnaire was conducted to the customers of Safartica in order to understand their motivating factors in visiting Lapland and if those factors would motivate them to visit in the low season. Using a SWOT analysis to evaluate the environment that Safartica operates in allows further understanding of the tourism industry in this region. The findings from the research, SWOT analysis and a thorough investigation into the Lapland tourism industry allows the author to make viable suggestions of new areas of operation for Safartica to consider as a remedy for improving tourism in the low season. The results from the research indicate that there is room for improvement during the low season with the cooperation from all those involved in the tourism industry in the local area. The author is able to indicate numerous areas where development is possible. One area for further research would be indigenous tourism, to understand if there would be any risks and if it is a viable option for development in Lapland.